Strategi Sekolah Dalam Menanamkan Nilai Antikorupsi Melalui Al Islam Kemuhammadiyahan Di SD Unggulan Muhammadiyah Lemahdadi - Suyitno; Trisna Sukmayadi (Program Studi Pendidikan Guru Sekolah Dasar, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Malang, 2022)
The case of corruption in Indonesia is very worrying. The more cases, the greater the loss borne by the state, so a great effort is needed to prevent it. Prevention can not only be done by the rule of law alone but also requires the participation of all parties. One of them is through school. Therefore, schools are an essential element in efforts to prevent corruption. Therefore, it requires a school strategy to teach anti-corruption values integrated through Al Islam Kemuhammadiyahan. This study describes the school's strategy for instilling anti-corruption education through Al Islam Kemuhammadiyahan at the Superior Elementary School of Muhammadiyah Lemahdadi Bangunjiwo Bantul. This research is qualitative descriptive research with a field research model. The data are presented descriptively with the observation method about the school's strategy in instilling anti-corruption values ​​integrated with Al Islam Kemuhammadiyahan in elementary schools. The data were obtained through interviews with the principal, vice chairman of the curriculum, and Al-Islam Kemuhammadiyahan teachers, as well as documentation in the form of documents or photos of activities. The data is analyzed by making the one obtained at school, filtered according to the fundamental theory, and presented in full according to the Miles and Huberman model. This study resulted in the concept that the school's strategy instilled anti-corruption values ​​in several ways, namely 1) guided by the school tagline